Asian observers in the Arctic framework: hits and misses. Issue 3 (27th May 2021) - Pareek, Nikhil
ABSTRACT: The presence and operation of observers, especially Asian observers in Arctic Council present a mixture of politics, science, diplomacy, geopolitics and other themes which propel certain reservations and anxieties in the Arctic states. The five Asian observers included in the 2013 Kiruna Ministerial meeting have performed distinctly in the last seven years with China among the East Asian states having caught the attention with unfounded allegations on its expansionist plans to take over the Arctic. The three East Asian observers have especially been constructively involved in future Arctic development through scientific research, international shipping and resource development. There are varying yardsticks and means being employed by the various Asian Arctic observers with little uniformity and embroiled with geopolitical competition among each other in different degrees, thus there is a deep cleft in the methodology and performance of the Asian observers.